2005
DOI: 10.1186/1478-7954-3-4
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric appendicitis rupture rate: a national indicator of disparities in healthcare access

Abstract: BACKGROUND: The U.S. National Healthcare Disparities Report is a recent effort to measure and monitor racial and ethnic disparities in health and healthcare. The Report is a work in progress and includes few indicators specific to children. An indicator worthy of consideration is racial/ethnic differences in the rate of bad outcomes for pediatric acute appendicitis. Bad outcomes for this condition are indicative of poor access to healthcare, which is amenable to social and healthcare policy changes. METHODS: W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
102
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(110 citation statements)
references
References 32 publications
6
102
2
Order By: Relevance
“…[8,9] Higher rupture rates have been reported in ethnic minority children, younger children, children with addresses from socioeconomically poorer ZIP codes, children who lack private insurance and children referred from somewhere other than a dedicated emergency department. [10] In our study cohorts, rural patients fared significantly worse than their urban counterparts. Both groups were black, thus eliminating issues of ethnicity or cultural practices as an explanation for disparate outcomes.…”
Section: Discussionmentioning
confidence: 93%
“…[8,9] Higher rupture rates have been reported in ethnic minority children, younger children, children with addresses from socioeconomically poorer ZIP codes, children who lack private insurance and children referred from somewhere other than a dedicated emergency department. [10] In our study cohorts, rural patients fared significantly worse than their urban counterparts. Both groups were black, thus eliminating issues of ethnicity or cultural practices as an explanation for disparate outcomes.…”
Section: Discussionmentioning
confidence: 93%
“…Multiple authors have reported that rates of rupture vary across racial lines, with minorities generally having higher rates. 2,[8][9][10] These differences have not been explained by differences in insurance or socioeconomic status. 11 However, others have shown that racial differences in ruptured appendicitis disappeared after adjusting for access to care.…”
Section: Racial Differencesmentioning
confidence: 96%
“…Similar to the Guagliardo et al [6], we found no evidence of an increase in appendiceal rupture with Hispanic patients who had Public Aid as their primary insurance (Correlation: 0.13; Odds Ratio: 0.5-1.1g; P value: 0.5853e). However, studies by Jablonski and Guagliardo [7] and Levas et al [8] indicate that there exists such an association which can be attributed to limited English proficiency, Hispanic ethnicity, lacking private insurance, referred from somewhere other than the ED, discharged from a teaching hospital, from poorer ZIP codes and discharged from a high-volume hospital. As suggested in a study Levas et al [8], equal access to care is the key to preventing any disparities in pediatric appendicitis outcome [9].…”
Section: Discussionmentioning
confidence: 91%
“…Identifying variables that can predict ruptured appendix remains crucial to ensure that the patient receives optimal care promptly. Many large databases, multicenter reviews have shown disparities in acute appendicitis and ruptured appendix based on variables such as ethnicity and socioeconomic status [6,7]. We attempted to study these variables, in addition to many others, in cases of appendicitis found in an urban community hospital setting.…”
Section: Resultsmentioning
confidence: 99%